Despesa pública: estrutura, função e controle judicial - Christopoulos, Basile Georges Campos (2009)
This paper tries to analyze the legal phenomenon of the public expenditure in Brazil, especially of the Budget, the juridic means by wich the State politics are formulated, and avaluate its importance to effectivate the constitutional rights, observing the direct relation between the appearance of generations of fundamental rights and the financial activity developed by the State. Tries to understand, on the basis of a proper and defined system of reference, the logical structure of the public expenditure and how the rule that disposes about it acts in the Brazilian positive law. It verifies the positivation process of the public expense, analyzing its structure and function, therefore, since the Federal Constitution until its effective payment. The analysis of the role of each of the three Powers evidences an hipertrofy of the Executive, that formulates and executes public politics many times in contradiction with the Legislative; the importance of the Legislative Power in the control and execution of the positivated by law, and the function of the Judiciary of controlling inspector of the Budget and the execution of the expenditures of the other public organs, establishing standards for the judge to take decisions about problems that involve public expenses and the efectivation of the State politics.